RANCANGAN MODEL PEMBERDAYAAN UMKM UNTUK MEMPERTAHANKAN KEARIFAN LOKAL DI KABUPATEN MAGELANG - Endang Kartini Panggiarti; Supanji Setyawan (Monex: Journal of Accounting Research, 2019)
The objective of this research is to find out and identify about village potention in Kabupaten Magelang. Kabupaten Magelang have 21 Kecamatan and 372 village. The researcher is only take 31 villages for sampel of the research. This research is qualitative research that explaining village potention in Kabupaten Magelang. The result of the research is most of the sampel that take the village are agrarian and depend on their live from agriculture, plantation, farming, and fishery. Some of the society of the villages have another business like handy craft and snack. Some of the villages have potention from natural and there is have 8 villages that have tourist destination are very interesting that can be develop. That villages have get coaching from relates parties, but less to put the villages become potention because they have low humanity, low knowledge and low motivation for create and develop their villages. So that need empowerment model to become the villages have a benefit potention.